PENERAPAN METODE STUDENT ACTIVE LEARNING (SAL) UNTUK MENINGKATKAN HASIL BELAJAR MATERI MENGENAL HURUF BESAR PADA ANAK USIA DINI - Cindy Cinthia (Ash-Shobiy: Jurnal Pendidikan Islam Anak Usia Dini dan Al-Qur'an, 2024)
This classroom action research aims to improve activities and learning outcomes in the material recognizing uppercase letters using the student active learning method. This research uses a Classroom Action Approach (PTK) with four main stages, namely planning, implementation, observation and reflection, which is carried out in two cycles. The subjects of this research were children aged 5-6 years in group B at RA Siti Amelia. Data collection techniques involve observation, tests, and documentation. The results of the research show an increase in both activities and student learning outcomes in each cycle. In cycle I, student learning activities increased from the results of pre-action activities, although not yet significantly with an average value of 75.46% in the active category. In cycle II, it was seen that student activity increased from the results of cycle I activities with an average score of 90.45% in the very active category. The learning outcomes have also increased. In the first cycle, there were 6 students out of 11 students who completed with a completion percentage of 54.54%. In cycle II, there was an increase in students who completed, amounting to 9 out of 11 students with a completion percentage of 81.82%. Thus, it can be concluded that the use of student active learning methods can improve student learning outcomes in the material of recognizing capital letters.